2013
DOI: 10.1089/neu.2012.2561
|View full text |Cite
|
Sign up to set email alerts
|

Calpain 1 Knockdown Improves Tissue Sparing and Functional Outcomes after Spinal Cord Injury in Rats

Abstract: To evaluate the hypothesis that calpain 1 knockdown would reduce pathological damage and functional deficits after spinal cord injury (SCI), we developed lentiviral vectors encoding calpain 1 shRNA and eGFP as a reporter (LV-CAPN1 shRNA). The ability of LV-CAPN1 shRNA to knockdown calpain 1 was confirmed in rat NRK cells using Northern and Western blot analysis. To investigate the effects on spinal cord injury, LV-CAPN1shRNA or LV-mismatch control shRNA (LV-control shRNA) were administered by convection enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
4
14
0
Order By: Relevance
“…The expression level of calpain markedly increases a few hours after SCI [39][40][41][42] , especially in motoneurons 43 . The activation of calpain 1, but not of calpain 2, contributes to initial reactive gliosis and tissue damage after SCI 40,44,45 , but calpain activity is confined to the injury site 46 . In regard to the calpain-mediated upregulation of I NaP , this observation is compatible with the small I NaP recorded in sacral motoneurons after acute SCI 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of calpain markedly increases a few hours after SCI [39][40][41][42] , especially in motoneurons 43 . The activation of calpain 1, but not of calpain 2, contributes to initial reactive gliosis and tissue damage after SCI 40,44,45 , but calpain activity is confined to the injury site 46 . In regard to the calpain-mediated upregulation of I NaP , this observation is compatible with the small I NaP recorded in sacral motoneurons after acute SCI 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of the first calpain in 1964 (Guroff, 1964), it is now recognized that the human genome contains 15 genes encoding calpain-like proteases (Sorimachi et al, 2010). The ubiquitously expressed μ - and m-calpain are a focus of investigation in the diseased nervous system (Bevers et al, 2010; Geddes and Saatman, 2010; Yu et al, 2013). μ - and m-calpain are heterodimers that consist of 80 kDa catalytic subunits sharing 55-65% sequence homology (calpain 1 and calpain 2, respectively) and a common 28 kDa regulatory subunit, known as calpain 4 or common small subunit 1 (CSS1; Goll et al, 2003).…”
Section: The Calpain/calpastatin Systemmentioning
confidence: 99%
“…Some studies have observed prosurvival roles for CAPN-1 activation but destructive roles for CAPN-2 activation in retinal ganglion cell degeneration [17,19]. However, in a recent rat contusive spinal cord injury model, CAPN-1 was activated and contributed to impaired locomotor function [16]. These differences might be explained by the preferential participation of CAPN isoforms to different cellular functions even in different substructures of the same cells [14,35].…”
Section: Discussionmentioning
confidence: 99%
“…Eleven types of calpain isoforms have been identified in humans so far, of which calpain-1 (µ-calpain, CAPN-1) and calpain-2 (m-calpain, CAPN-2) are the most widely ubiquitous isoforms in the central nervous system (CNS) [13]. Being distributed in the same subcellular localization (cytoplasm) and sharing a common small subunit (known as CAPN-4) upon activation, CAPN-1 and CAPN-2 seem to have similar biochemical properties [13,16]. CAPN-1 and CAPN-2 have previously been demonstrated to be overactivated in various models of neurodegenerative diseases and injury, although they require micromolar and millimolar calcium levels for activation, respectively [13,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation